Strategies for Regulating the Bioavailability and Mobility of Se and Cd in Cd-Contaminated Seleniferous Soils: Coupling the Bioavailable Se:Cd Molar Ratio with Soil Properties - Zebin Tan; Qinlei Rong; Wenfeng Wang; Haiyan Jiang; Luyao Yu; Jingrui Hu; Jie Chen; Xuefeng Liang; Xiaomin Zhao; Chunhuo Zhou (Agronomy)
The prevalent issue of cadmium (Cd) in naturally selenium (Se)-enriched soils has significantly impacted the safe utilization of Se-rich soils. Although Se antagonizes Cd and is affected by Se:Cd stoichiometry, the mechanism behind this interaction remains unclear. To reveal the relation between the soil bioavailable Se:Cd molar ratio (AMR-Se:Cd) and the transformation of Se and Cd fractions, as well as to identify the principal controlling factors, we conducted a study in Shanggao County, Yichun City, a naturally Se-rich area in Jiangxi Province, and quantitatively analyzed the distribution features of Se, Cd, and AMR-Se:Cd across different soil types and land use types. The results demonstrated that soil AMR-Se:Cd was statistically positively correlated with the bioavailable Se content (r = 0.331, p < 0.01) and had a negative correlation with the bioavailable Cd content (r = −0.402, p < 0.001). Cd was transformed from highly bioavailable fractions to less bioavailable fractions as the AMR-Se:Cd increased. A suitable AMR-Se:Cd was conducive to achieving a higher mobility of Se (mobility factor of 12.31%) and a lower mobility of Cd (mobility factor of 23.49%) simultaneously. Spearman correlation analysis and partial least squares path modeling revealed that soil type and land use type modulated the morphological transformation of soil Se and Cd by influencing changes in free Fe-Al oxides and soil organic matter content, which in turn altered the AMR-Se:Cd. Therefore, the findings of this study can offer guidance for regulating the appropriate AMR-Se:Cd in Se-rich soils through management practices to enhance the bioavailability and mobility of soil Se while diminishing the bioavailability and mobility of Cd.